2014
DOI: 10.1111/bju.12610
|View full text |Cite
|
Sign up to set email alerts
|

A randomised controlled trial comparing use of lignocaine periprostatic nerve block alone and combined with diclofenac suppository for patients undergoing transrectal ultrasound (TRUS)‐guided prostate biopsy

Abstract: ObjectiveTo examine whether or not the combination of diclofenac suppository with peri-prostatic nerve block (PPNB) was effective in reducing the degree of pain experienced during transrectal ultrasound (TRUS)-guided prostate biopsy in a randomised single-blind placebo-controlled trial. Patients and MethodsIn all, 96 patients having a planned TRUS-guided prostate biopsy were randomised into one of the following arms on a 1:1 basis: 10 mL 1% lignocaine PPNB and placebo suppository (control) or 10 mL 1% lignocai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 28 publications
2
11
0
Order By: Relevance
“…Conversely, in our study, prostate volume did not effect VAS scores in both groups. In the prostate biopsy, various other analgesia methods were investigated using intravenous conscious sedation (fentanyl and midazolam), nitrous oxide inhalation, oral analgesia (paracetamol/codeine), intrarectal diclofenac and 40% dimethyl sulfoxide [22,23]. Obek et al showed a meaningful reduced level of pain with local lidocaine gel application before PPNB whereas tradamol and periprostatic blockage had similar effects [24].…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, in our study, prostate volume did not effect VAS scores in both groups. In the prostate biopsy, various other analgesia methods were investigated using intravenous conscious sedation (fentanyl and midazolam), nitrous oxide inhalation, oral analgesia (paracetamol/codeine), intrarectal diclofenac and 40% dimethyl sulfoxide [22,23]. Obek et al showed a meaningful reduced level of pain with local lidocaine gel application before PPNB whereas tradamol and periprostatic blockage had similar effects [24].…”
Section: Discussionmentioning
confidence: 99%
“…For prostate cancer diagnosis, the current standard method is taking a core biopsy from prostate tissue by transrectal ultrasound guidance. During this procedure, which can be very painful, many topical analgesics, such as lignocaine gel, glyceryl trinitrate and analgesia methods, such as an eutectic mixture of local anaesthetics (EMLA) cream, intravenous or inhalation anaesthesia, periprostatic nerve block, and oral or intrarectal analgesics are used [ 4 , 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…For VAS of both probe manipulation and needle biopsy pain, the analyses showed only slight changes in the precision of the effect estimate with sequential exclusion of each study from the analysis. Exclusion of two retrospective studies 12,25 and four abstracts 19,20,23,24 resulted in a slightly decreased WMD of −2.12 (95% CI −2.98 to −1.44, P < 0.001) for probe manipulation pain and −0.56 (95% CI −0.82 to −0.40, P < 0.001) for needle biopsy pain compared with the original effects.…”
Section: Sensitivity Analysismentioning
confidence: 92%
“…Six studies used lidocaine gel 4,10-14 for IRLA, six used lidocaine-prilocaine cream, [15][16][17][18][19][20] three used GTN ointment [21][22][23] and three used a diclofenac suppository. 6,24,25 PPNB was accomplished by a 22-G needle under ultrasound guidance into the neurovascular bundle at the base of the prostate, just lateral to the junction between the prostate and seminal vesicle bilaterally in all, but not specified in three studies.…”
Section: Description Of Studiesmentioning
confidence: 99%
See 1 more Smart Citation